Effect of pharmaceuticals on the performance of a novel osmotic membrane bioreactor (OMBR) - Wang, Rong (2013)
The integration of forward osmosis (FO) and biological process, known as the osmotic membrane bioreactor (OMBR), may be viewed as beyond the state of the art for used water treatment and water reclamation. While it is known that the OMBR is able to produce good product water quality in terms of total organic carbon (TOC) removal, limited information is available on the removal of organic micro-pollutants in relation to process performance under the concentrated environment. In this study, a novel OMBR system was continuously operated over 73 days, during which pharmaceuticals were dosed on two occasions into the system. It was found that while pharmaceutical removal was high (>96%), other process parameters in the form of TOC, mixed liquor suspended solids (MLSS) and extracellular polymeric substances (EPS) were unmistakably affected. The major portion of TOC that permeated the FO membrane was found to be low-molecular weight neutral compounds which were associated with the impaired biological process. Microbiological analysis confirmed shifts in microbial populations occurred due to the increased salinity and dosage of the pharmaceuticals. The study demonstrated the importance of the biological process for optimal OMBR system performance, and paves the way for further research in this direction.